EVALUASI PENERAPAN BELANJA MODAL BERDASARKAN PERATURAN PEMERINTAH NO. 12 TAHUN 2019 DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MINAHASA - Tendean, Lanny; Tinangon, Jantje J.; Datu, Christian V. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
ABSTRACTCapital expenditure is one type of regional expenditure that is arranged in the district/city APBD. According to Government Regulation Number 12 of 2019, capital expenditure is a budget expenditure for the acquisition of fixed assets and other assets that provide benefits for more than 1 (one) accounting period. The types of capital expenditures in question are land expenditures; shopping for equipment and machinery; building and building expenditures; road, irrigation and network spending; expenditure on other fixed assets; and other asset purchases. This study aims to determine whether the application of capital expenditure in the Department of Population and Civil Registration of Minahasa Regency is in accordance with Government Regulation Number 12 of 2019. This type of research is descriptive qualitative. Data collection techniques with document studies and interviews. Data analysis is done by reducing, presenting, verifying, and analyzing. The results showed that the implementation of capital expenditure at the Department of Population and Civil Registration of Minahasa Regency was in accordance with Government Regulation No. 12 of 2019. It is recommended that there should be smoother coordination between the agency and the TPAD so that later there will be no difference between the proposed RKA and the realization of the DPA.